Pengenalan Budaya Sumatera Utara Melalui Permainan Kincir Angka pada Pemelajar BIPA: Introduction to North Sumatra Culture Through the Number Wheel Game for BIPA Students - Hera Sapira Br Karo; Maya Rani Manurung; Dian Syahfitri (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Culture is the result of human thought that can be in the form of objects or actions, which need to be preserved in order to maintain the nation's historical heritage. This study focuses on the introduction of two ethnic groups, namely Batak Toba and Batak Karo. In Batak Toba, marriage customs are one of the prominent cultures in the lives of the Batak Toba people. Meanwhile, Batak Karo has a typical food, namely Cimpa. The uniqueness of these two cultures enriches the diversity of Indonesian customs that attract the attention of many people, including foreign speakers. BIPA teaching research aims to help foreign learners achieve the ability to communicate in Indonesian well and correctly. The focus of this study is to introduce the culture of North Sumatra, especially the Batak Toba and Batak Karo cultures, through the Kincir Angka game. This study uses a qualitative descriptive method, namely an approach that aims to explore or describe the social situation as a whole. Based on the results of the study, it can be concluded that the Kincir Angka game is effective in helping BIPA (Indonesian for Foreign Speakers) learners understand and get to know the culture of North Sumatra, especially the culture of the Batak Toba and Batak Karo tribes. The results of the trial showed that the use of this game can improve learners' memory of cultural elements, such as traditional Batak Toba clothing and typical Batak Karo food. The application of the Kincir Angka game as a learning medium helps overcome the limitations in teaching culture that are often faced by BIPA teachers and makes it easier for learners to match visual information with words in Indonesian.